Uslub al-Qur’an: Studi Uslub Taqdim wa Ta’khir dalam al-Qur’an - Muhammad Subhi Mahmasoni (Program Studi Bahasa dan Sastra Arab Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
Uslub is a method of selecting and using words so as to produce a certain understanding for the reader. With the characteristics of uslub al-Qur'an, the audience will be touched by their thoughts and emotions. This is because the uslub al-Qur'an is actually i'jaz al-Qu'ran itself. This large number of uslub al-Qur'an becomes important when it is associated with the existing rules of interpretation so that there is no inequality in interpreting, interpreting and understanding a verse of the Qur'an. From there, it can be imagined that actually uslub is very decisive and plays an important role in interpretation, especially regarding issues of interpretation, meaning and understanding of the literary language of the Qur'an itself.